(untitled) (Journal of Forest and Livelihood, 2009)
This paper draws on the experiences of the buffer zone management programme in Nepal. Although the programme is the result of changing international conservation discourses, it has evolved in Nepal’s unique socio-political and environmental contexts as a response to continued resource conflict in and around protected areas. The implementation process and the outcomes of the programme have been mediated by a wide array of social actors, resulting in gaps in policy intent and outcomes. The experiences show that important achievements have been gained, mainly in contributing to resource regeneration, community development and facilitating local institutional strengthening for participatory conservation. This paper discusses the links between policy, strategies and specific outcomes of the programme. This is followed by a discussion of the emerging issues and challenges and the strategies taken to address them. Finally, the paper draws some key lessons from the programme and suggests a way forward to better realise conservation with livelihoods. Key words: buffer zone, conservation, livelihoods, participation, policy Full text is available at the ForestAction website Journal of Forest and Livelihood 6(2) September 2007 pp.44-53